Impacts of combination of onion bulb, holy basil and turmeric rhizome on shelf- life, flesh and microbial quality of smoked Clarias gariepinus - Sunday Emmanuel Olusola; Toyosi Elizabeth Martins (Aceh Journal of Animal Science, 2023)
The increasing use of synthetic antimicrobials has created a situation leading to a pond ecological imbalance and enrichment of multiple multi-resistant pathogenic microorganisms. This study was conducted to investigate the impact of spices and natural preservatives using a mixture of Onion Bulb (OB), Holy Basil (HB) and Turmeric Rhizome (TR) on shelf–life, flesh and microbial quality of smoked Clarias gariepinus during 56 days storage. Spices were added at the point of processing with five treatments of 8 fresh C. gariepinus (1.2-2kg) were distributed into experimental containers; the control (without Onion Bulb, Holy Basil and Turmeric Rhizome), (TR + OB)2, (TR+ HB)3, (OB +HB)4, (TR + OB + HB)5 and the experiment were carried out in triplicates. Clarias gariepinus were smoked in a smoking kiln at 40ºC- 60ºC and 120-150ºC for 6 and 18 hours respectively. Proximate composition, biochemical parameters, organoleptic assessment, and microbial analysis were carried out using standard methods. The result showed that the crude protein of C. gariepinus was higher in the treated groups compared to the control. Also, the result shows that the biochemical parameters, organoleptic assessment and the microbial loads in smoked C. gariepinus were reduced in the treated groups than in the control at 1 day, 28 days and 56 days storage respectively. The results indicated that using onion bulb, holy basil, and turmeric rhizome in combination may be useful in improving the shelf life, consumer acceptability of smoked C. gariepinus and preventing bacteria pathogens in smoked C. gariepinus.Keywords: Catfish, Onion Bulb, Holy Basil, Microbial Loads, Turmeric Rhizome